Modificirana metoda deformacijske analize po postopku münchen - Savšek, Simona (Geodetski vestnik, 2023)
Despite the technical progress monitoring the stability of engineering structures remains one of the most difficult tasks in engineering geodesy. This article presents the deformation analysis according to the Munich approach of W. M. Welsch. The method deals with the testing of the geodetic network's congruence, the affinity of selected triangles, and the testing of other kinematic parameters in 2D geodetic networks. Deformation analysis using the Munich approach can be performed using the X-method, which is based on the comparison of the coordinates of identical points in the geodetic network between two sets of measurements that depend on the geodetic datum, or using the L-method, which determines changes in the values of lengths and angles which are quantities independent of the geodetic datum. In the modified method, we propose to determine the congruence of all lengths and all angles in the network between two sets of measurements and to determine the congruence of all triangles between points in the network, not only selected ones, as it is common in the classical approach of deformation analysis based on the Munich approach. The proposed improvements are tested on the example of a known hexagon, and an analysis is made of the success of detecting stable points in the network using the classical Munich approach. In the present case, the results of the proposed method did not differ from the results of other deformation analysis methods.
Keywords: deformacijska analiza; deformation analysis; L-method; metoda L; metoda X; modificirana metoda; modified method; Munich approach; postopek München; strain analysis of triangles; testing of congruence; testiranje preoblikovanja trikotnikov; testiranje skladnosti; X-method